Концепція прийнятного ризику в питному водопостачанні міст - Василенко, С.Л.; Волошкіна, О.С. (Екологічна безпека та природокористування, 2009)
The theoretic-applied aspects of application conception of acceptable risk at internal and external levels of security are considered for municipal drinking water supply systems.